A rare cause of severe lactic acidosis. (24th April 2015) - Saeed, Saad; Kuravi, Aditya; Rowley, Matt; Saeed, Marwa
Abstract : Sarcoidosis is a multisystem disease of unknown aetiology with a classic histology of non-caseating granulomas. It most often occurs in those below the age of 50 years, and has a female preponderance. The main targets, often symptomless, are the lung and hilar lymph nodes, although liver involvement is not uncommon. Hepatic sarcoidosis encompasses a broad spectrum of presentations, from asymptomatic hepatic granulomas with slight liver function test derangement to severe liver involvement with cholestasis, advanced liver cirrhosis or chronic liver failure. Mortality due to acute liver failure is far less common than lung and heart involvement. We describe a case of fulminant liver failure with multiorgan failure presenting initially with chronic non-specific symptoms, in addition to minimal abnormal investigations such as mild anaemia, neutrophil leucocytosis and mild obstructive liver dysfunction. Presenting features included confusion, hypotension, oliguria and rapidly deteriorating liver function with severe lactic acidosis. Postmortem examination confirmed extensive systemic sarcoidosis.